2014
DOI: 10.1371/journal.pone.0110365
|View full text |Cite
|
Sign up to set email alerts
|

L-Endoglin Overexpression Increases Renal Fibrosis after Unilateral Ureteral Obstruction

Abstract: Transforming growth factor-β (TGF-β) plays a pivotal role in renal fibrosis. Endoglin, a 180 KDa membrane glycoprotein, is a TGF-β co-receptor overexpressed in several models of chronic kidney disease, but its function in renal fibrosis remains uncertain. Two membrane isoforms generated by alternative splicing have been described, L-Endoglin (long) and S-Endoglin (short) that differ from each other in their cytoplasmic tails, being L-Endoglin the most abundant isoform. The aim of this study was to assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 50 publications
1
26
0
8
Order By: Relevance
“…In agreement with these reports, our present data in the UUO model of tubulo-interstitial fibrosis shows the increase in both Eng mRNA and protein expression in the O kidney ( Figure 1). Several authors demonstrated that Eng promotes fibrosis in different kidney experimental models [15,16,[33][34][35][36][37] and other experimental models of tissue fibrosis in organs such as heart [13,38], liver [39] or skin [40]. Two different Eng isoforms that differs exclusively in the intracellular tail have been reported in both humans [18] and mice [19].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In agreement with these reports, our present data in the UUO model of tubulo-interstitial fibrosis shows the increase in both Eng mRNA and protein expression in the O kidney ( Figure 1). Several authors demonstrated that Eng promotes fibrosis in different kidney experimental models [15,16,[33][34][35][36][37] and other experimental models of tissue fibrosis in organs such as heart [13,38], liver [39] or skin [40]. Two different Eng isoforms that differs exclusively in the intracellular tail have been reported in both humans [18] and mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that L-and S-Eng differentially modulate the TGF-β1 signaling pathway [20,21]. A previous study from our group demonstrated that L-Eng overexpression increases renal fibrosis after unilateral ureteral obstruction (UUO) [16].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations